Arsenic Combined With All-Trans Retinoic Acid for Pediatric Acute Promyelocytic Leukemia: Report From the CCLG-APL2016 Protocol Study. Issue 28 (1st October 2021) - Zheng, Huyong; Jiang, Hui; Hu, Shaoyan; Liao, Ning; Shen, Diying; Tian, Xin; Hao, Guoping; Jin, Runming; Li, Jianxin; Fang, Yongjun; Ju, Xiuli; Liu, Ansheng; et al.
Abstract : PURPOSE: Arsenic combined with all-trans retinoic acid (ATRA) is the standard of care for adult acute promyelocytic leukemia (APL). However, the safety and effectiveness of this treatment in pediatric patients with APL have not been reported on the basis of larger sample sizes. METHODS: We conducted a multicenter trial at 38 hospitals in China. Patients with newly diagnosed APL were stratified into two risk groups according to baseline WBC count and FLT3-ITD mutation. ATRA plus arsenic trioxide or oral arsenic without chemotherapy were administered to the standard-risk group, whereas ATRA, arsenic trioxide, or oral arsenic plus reduced-dose anthracycline were administered to the high-risk group. Primary end points were event-free survival and overall survival at 2 years. RESULTS: We enrolled 193 patients with APL. After a median follow-up of 28.9 months, the 2-year overall survival rate was 99% (95% CI, 97 to 100) in the standard-risk group and 95% (95% CI, 90 to 100) in the high-risk group ( P = .088). The 2-year event-free survival was 97% (95% CI, 93 to 100) in the standard-risk group and 90% (95% CI, 83 to 96) in the high-risk group ( P = .252). The plasma levels of arsenic were significantly elevated after treatment, with a stable effective level ranging from 42.9 to 63.2 ng/mL during treatment. In addition, plasma, urine, hair, and nail arsenic levels rapidly decreased to normal 6 months after the end of treatment. CONCLUSION: Arsenic combined with ATRA is effective and safe in pediatric patients with APL, although long-term follow-up is still needed.